Money games : the inside story of how American dealmakers saved Korea's most iconic bank - Shan, Weijian, 1953- (John Wiley & Sons, Inc., 2021)
"To private equity investors, the making of a deal, no matter how big, complex or high profile, is only the beginning. The success or failure of the investment can only be ascertained when the investor fully exits. In between, teams of private equity professionals expend great amounts of energy and resources to create value with the acquired company, to transform it and to grow it. To exit from a big investment is often as complicated a deal as the initial acquisition -- if not more so. Any mistake in this deal cycle can lead to disaster and financial losses, erasing whatever satisfaction the closing of the transaction brought years prior, and possibly ending the careers of the dealmakers themselves. A seasoned private equity investor knows that in every deal, he is walking on thin ice with a heavy load on his shoulders, taking great care with every step to avoid falling into darkness. He can celebrate only after reaching the far shore and delivering his load to his investors."--